Gross Anatomy of Wing and Pelvic Limb Bones in Emu (Dromaius novaehollandiae) - Kumar, Pawan; Singh, Gurdial (Indian Journal of Veterinary Anatomy, 2014)
The gross anatomy of bones of wing and pelvic limb was studied in adult emus. Salient morphologicalcharacteristics have been discussed. Structural differences between bones of the emu and fowl will not onlystrengthen the anatomical knowledge which will contribute to understand functional aspects of musculoskeletalsystem but also form a data base for applications to design clinically oriented orthopedic models applicable tohumans.